HIGH FRUCTOSE DIET INCREASES RENAL CHREBP-BETA EXPRESSION AND LEADS TO INTRA-RENAL FAT ACCUMULATION IN A METABOLIC-LIKE SYNDROME RAT MODEL. (June 2022) - Leibowitz, Avshalom; Bier, Ariel; Shpira, Eli; Khashab, Rawan; Sharabi, Yehonatan; Grossman, Ehud
Abstract : Objective: A high fructose diet induces metabolic syndrome (MeS) which includes ectopic lipid accumulation, such as fatty liver. MeS is also associated with chronic kidney disease (CKD). A novel isoform of ChREBP, ChREBPb, was recently reported to regulate liver fructose metabolism that leads to fatty liver development. The aim of this study was to evaluate fructose metabolism in the kidney and whether this metabolism leads to intra-renal fat accumulation. Design and method: In-vivo: Sprague Dawley rats were fed either normal chow (Ctrl) or a high fructose diet (HFrD) for eight weeks. Blood pressure, fasting blood glucose and triglycerides were measured. The kidneys were harvested for ChREBPb and de novo lipogenesis (DNL) gene expression, triglyceride content and histopathology staining. In-vitro: HK2 (human kidney) cells were treated with fructose for 48 h and gene expression for ChREBPb and DNL were determined. Results: The HFrD rats exhibited higher blood pressure (152 vs. 138 mmHg), glucose (146 vs. 127 mg/dl) and triglyceride (280 vs. 143 mg/dl) levels. Kidneys weight normalized to body weight of the HFrD rats were significant higher than the Ctrl (7.32 vs. 5.87). The difference can be explained by the higher triglyceride content in the HFrD kidneys (16.4 vs. 12.4 mg). Oil red staining revealed higher lipid droplet formation in the HFrD kidneys, which was also supported by higher adipophilin mRNA expression. The expression level of ChREBPb and its downstream genes, scd and fasn, were elevated in the HFrD kidney. Treating HK2 cells with 40 mM fructose increased ChREBPb expression levels. Its downstream genes, fasn and acc, also showed an increasing trend. In three out of five experiments, adipophilin was increased as well. Conclusions: In this study, we demonstrated that fructose consumption leads to intra-renal lipid accumulation and to the formation of a fatty kidney. This suggests a potential mechanism that can partially explain CKD development in fructose induced MeS.